Reverse Engineering to Design an Ergonomic Bio Briquette Packaging Machine - Taufan Maulana Rizaldy; Agus Kusnayat; Yusuf Nugroho Doyo Yekti (International Journal of Innovation in Enterprise System, 2023)
Briquettes are solids that are produced through the process of compression and pressure applicationand if burned will produce a small amount of smoke. Briquette production is carried out using ahammer mill where the raw material for briquettes is charcoal which is then crushed into charcoalgranules. The packaging process is still done manually using a shovel to fill the 50kg sack and thentake it to the sewing machine. The worker's posture when using a shovel has a Rapid Entire BodyAssessment (REBA) score of 12 so it has a high work risk of musculoskeletal disorders (MSDs) andrequires immediate improvement. The working environment at the company produces pollutants,meaning that there is no capture container for the fall of charcoal grains from the hammer mill. Basedon the existing problems, a redesign of the existing machine is needed. The proposed machine wasdesigned using the Reverse Engineering method because the existing condition already uses themachine then the existing machine is decomposed to find out the components and functions of theexisting machine to find alternative concepts. The ergonomic approach uses REBA and LBA todetermine changes in worker posture and the forces acting in the human spine. The DEM approachwas chosen to find out if the charcoal grains dropped from the hammer mill were successfully capturedand to find out the flow of the charcoal grains. The results of the proposed machine design have agood impact on workers in the packaging process.